Pertencer e deslocar virtualmente: Teletandem como espaço antropofágico - Buvolini, Paola C. F [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Teletandem is a virtual, autonomous and collaborative context of teaching and learning foreign languages and cultures that is mediated by computer using VOIP (Voice Over Internet Protocol) technology software, such as Skype or Google Hangout. Within this context, pairs of students collaborate with each other in learning their respective native languages or language of competence (no need to be a native speaker of the target language). Learners use the voice, text and webcam image features of Skype. The study is about the subjectivities these pairs of virtual interactants. We tried to verify how their subjectivities are marked by historical phenomena such as globalization and the use of educational technology. For this, we used the learners' utterances that suggest (or not) national identities as symbols of differences of these subjects. We set out this objective by having the following presuppositions in mind: (a) the content of the teletandem interactions focuses both on the contrast and the marking of differences between the interactants' countries; and (b) the participants' discussions on such differences are often repetitive, common sense and essentialist in their nature and they can produce stereotypes of nationalities. The guiding research question is: What are the subjective effects of comparing national identities in interactions via teletandem? Theoretically, the study is based on theories of identity and subject proposed by Hall, Smith and Bauman, on studies about subjectivities brought by Rolnik, Deleuze and Guattari, and on Judith Butler's studies about performativity (these anchored on Derrida's concepts of sedimentation, citationality and iterability). Thus, we sought to know part of the learners' subjectivities who participate in this virtual, autonomous and collaborative practice of teletandem. We adopted a qualitative methodology in the format of three exploratory case studies. Data were collected through video ...

Teletandem é um contexto virtual, autônomo e colaborativo de ensino e aprendizagem de línguas e culturas estrangeiras mediado pelo computador que utiliza aplicativos de tecnologia VOIP (Voice Over Internet Protocol), como o Skype ou Google Hangout. Neste contexto, utilizando os recursos de voz, texto e imagens de webcam (dentre outros), pares de alunos colaboram um com o outro na aprendizagem de suas respectivas línguas nativas ou de competência (não é necessário ser falante nativo da língua-alvo). O objetivo desta dissertação é investigar as subjetividades dos interagentes constituídos como pares na tentativa de verificar como essas subjetividades são marcadas por fenômenos históricos como a globalização e a tecnologia na educação. Para isso, usamos os enunciados que trazem (ou não) a identidade nacional como símbolo de diferença desses sujeitos. Tal objetivo partiu das seguintes constatações: (a) os conteúdos das interações em teletandem centram-se no contraste e na marcação de diferenças entre os países dos interagentes e (b) as discussões entre os participantes sobre tais diferenças são frequentemente repetitivas, de senso comum e essencialistas por natureza, podendo produzir estereótipos de nacionalidades. A pergunta norteadora da pesquisa é: quais são os efeitos subjetivos da comparação de identidades nacionais nas interações via teletandem? Teoricamente, o estudo está fundamentado nas teorias de identidade e sujeitos trazidos por Hall, Silva, Bauman, nos estudos de subjetividades trazidos por Rolnik, Deleuze e Guattari e nos estudos sobre performatividade da filósofa Judith Butler, esses ancorados nas ideias de sedimentação, citacionalidade e iterabilidade trazidas por Derrida. Assim, buscamos conhecer parte das subjetividades dos aprendizes que participam dessa prática virtual, autônoma e colaborativa do teletandem. O estudo adota metodologia qualitativa, com formato de três estudos...
Keywords: Linguistica aplicada; Professores de linguas - Formação; Sujeito (Filosofia); Identidade; Educação e globalização; Subjetividade; Ensino a distância - Ensino auxiliado por computador; Applied linguistics